All about the Money – External Performance Monitoring is Affected by Monetary, but Not by Socially Conveyed Feedback Cues in More Antisocial Individuals - Pfabigan, Daniela M.; Alexopoulos, Johanna; Bauer, Herbert; Lamm, Claus; Sailer, Uta (Frontiers in Human Neuroscience, 2011)
This study investigated the relationship between feedback processing and antisocial personality traits measured by the PSSI questionnaire (Kuhl & Kazén, 1997) in a healthy undergraduate sample. While event-related potentials (Feedback Related Negativity [FRN], P300) were recorded, participants encountered expected and unexpected feedback during a gambling task. As recent findings suggest learning problems and deficiencies during feedback processing in clinical populations of antisocial individuals, we performed two experiments with different healthy participants in which feedback about monetary gains or losses consisted either of social-emotional (facial emotion displays) or non-social cues (numerical stimuli). Since the FRN and P300 are both sensitive to different aspects of feedback processing we hypothesized that they might help to differentiate between individuals scoring high and low on an antisocial trait measure. In line with previous evidence FRN amplitudes were enhanced after negative and after unexpected feedback stimuli. Crucially, participants scoring high on antisocial traits displayed larger FRN amplitudes than those scoring low only in response to expected and unexpected negative numerical feedback, but not in response to social-emotional feedback - irrespective of expectancy. P300 amplitudes were not modulated by antisocial traits at all, but by subjective reward probabilities. The present findings indicate that individuals scoring high on antisociality attribute higher motivational salience to monetary compared to emotional-social feedback which is reflected in FRN amplitude enhancement. Contrary to recent findings, however, no processing deficiencies concerning social-emotional feedback stimuli were apparent in those individuals. This indicates that stimulus salience is an important aspect in learning and feedback processes in individuals with antisocial traits which has potential implications for therapeutic interventions in clinical populations.